If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + x = 4 + -3x Solving -8 + x = 4 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -8 + x + 3x = 4 + -3x + 3x Combine like terms: x + 3x = 4x -8 + 4x = 4 + -3x + 3x Combine like terms: -3x + 3x = 0 -8 + 4x = 4 + 0 -8 + 4x = 4 Add '8' to each side of the equation. -8 + 8 + 4x = 4 + 8 Combine like terms: -8 + 8 = 0 0 + 4x = 4 + 8 4x = 4 + 8 Combine like terms: 4 + 8 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| 2e^3x+3=4 | | 4w-3w-1=13 | | 3xy/3xy | | 32=-2+34 | | f(1)=1.5*x^3 | | -3p+(-7p)=-10 | | x^2-0.08658008658x+0.0001623376=06 | | f(x)=1.5*x^3 | | 12x+3(5-4x)=15 | | 15j-15j+2j-2=18 | | -12+2x=8-3x | | (x+3)(3x-1)= | | 16y-15y=11 | | T-0.95=1.25 | | 9x=(80-x) | | -2.5+K=-3.7 | | 8-y-3=4 | | -5x+1=-3x-7 | | -4.5=9.5+C | | 2-loge(x-3)=0 | | 40n+260= | | -9+3x=3-x | | 3/g=5.3/16 | | -v+(-16v)-(-15v)=6 | | -.25+X=-.25 | | 4c^3-12c^2=160c | | 6q+1q=896 | | 10(5x-11)=390 | | x+(-5.75)=-10.25 | | 2-ln(x-3)=0 | | 3n^2+2n-3=0 | | -22x+21=8x^2 |